Evaluasi Pembelajaran Sosiologi secara Daring pada Masa Pandemi Covid-19 di SMA Negeri 1 Pangkalan Kuras - Nurshella Nurshella; Ike Sylvia (Universitas Negeri Padang, 2022)
The purpose of this study was to describe the results of the evaluation of the implementation of online sociology learning during the Covid-19 pandemic at SMA Negeri 1 Pangkalan Kuras. This research is motivated because the application of learning that was originally face-to-face at school became online learning. During the implementation of online learning, there are obstacles that occur to students so that an evaluation process is needed for the implementation of online learning. This research is quantitative research using evaluation research type. The type of evaluation used is program evaluation. This study uses a descriptive evaluative research method with a quantitative-descriptive approach. The research instrument used is a questionnaire. Based on the research results obtained as a whole, the results of the evaluation of online learning programs carried out by students and teachers went well. And the online sociology learning program can be continued with a slight improvement in the process of giving and understanding material to students.